2021
DOI: 10.21203/rs.3.rs-145764/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and Eating Problems in Daily Life: the Mediating Roles of Stress, Negative Affect and Posttraumatic Stress Symptoms

Abstract: BackgroundThe 2019 coronavirus disease (COVID-19) epidemic poses a challenge to individuals' mental health. Increased stress, negative affect (NA), and posttraumatic stress symptoms (PTSS) that are being experienced globally may lead to eating problems. The purpose of this study was to explore the impacts of the perceived severity of COVID-19 on eating problems as well as the mediating effects of stress/NA/PTSS both at the within-person level and between-person level. MethodsDuring the COVID-19 outbreak, a tot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…It has been theorized that individuals with eating disorders (EDs) may be especially susceptible to greater levels of distress due to pandemic restrictions and an exacerbation of pre-existing ED symptoms prior to COVID-19 ( Touyz et al, 2020 ). Changes to routine, reduced social contact and access to professional support/treatment for their disorder, along with food scarcity, may serve to worsen or trigger ED symptoms ( Sheng et al, 2021 ). In an Australian study, Phillipou et al (2020) recruited 180 participants who self-identified as having an eating disorder of any kind, as well as individuals from the general population.…”
Section: Introductionmentioning
confidence: 99%
“…It has been theorized that individuals with eating disorders (EDs) may be especially susceptible to greater levels of distress due to pandemic restrictions and an exacerbation of pre-existing ED symptoms prior to COVID-19 ( Touyz et al, 2020 ). Changes to routine, reduced social contact and access to professional support/treatment for their disorder, along with food scarcity, may serve to worsen or trigger ED symptoms ( Sheng et al, 2021 ). In an Australian study, Phillipou et al (2020) recruited 180 participants who self-identified as having an eating disorder of any kind, as well as individuals from the general population.…”
Section: Introductionmentioning
confidence: 99%